Pembangunan berwawasan kependudukan dan keluarga: sebuah percikan pemikiran - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1997)
Abstract The concept formulation of the -development having population and family concepts aims at shifting the concept of population from a burden connotation. into the development performer. The problems which are often seen in achieving the goal is among other thing: the existence of collision between the reinforcement of family functions with values and interests of other concept, such as economy. Agus Dwiyanto